Association Between Feeding Guidelines and Stunting Among Children Aged 6–24 Months - Sulistia Tasya; Fransiska Farah (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2025)
Stunting is a chronic nutritional problem commonly found in children aged 6–24 months due to prolonged inadequate nutrient intakeAnother factor contributing to stunting is suboptimal feeding practices. This study measures the quality of feeding (feeding rules) through three key aspects: consistency of meal schedules, responsive feeding techniques, and mealtime environment arrangement. The assessment in this study uses a questionnaire based on Chatoor's scale of 1-9, where a score of 7-9 indicates good practices, 4-6 falls into the moderate category, and 0-3 signifies low quality. This study aimed to determine the relationship between feeding rules and stunting among children aged 6–24 months at Grogol Petamburan Health Center, West Jakarta. Using a cross-sectional design and quantitative approach, the study involved 133 mothers and their children, selected through total sampling. Data were collected via questionnaires and anthropometric measurements. Results showed that 21.8% of children were stunted. The proportion of stunting was higher among mothers with poor feeding rule practices (36.4%) compared to those with moderate–good practices (17.0%). A significant relationship was found between feeding rules and stunting (p = 0.019; OR = 2.79; 95% CI = 1.157–6.730). It can be concluded that proper feeding rule implementation plays a key role in preventing stunting.